Association of industry ties with outcomes of studies examining the effect of wholegrain foods on cardiovascular disease and mortality: systematic review and meta-analysis. Issue 5 (19th May 2019) - Chartres, Nicholas; Fabbri, Alice; McDonald, Sally; Turton, Jessica; Allman-Farinelli, Margaret; McKenzie, Joanne; Bero, Lisa
Abstract : Objective: To determine if observational studies examining the association of wholegrain foods with cardiovascular disease (CVD) with food industry sponsorship and/or authors with conflicts of interest (COI) with the food industry are more likely to have results and/or conclusions that are favourable to industry than those with no industry ties, and to determine whether studies with industry ties differ in their risk of bias compared with studies with no industry ties. Design: Systematic review and meta-analysis of observational studies. Data sources: We searched eight databases from 1997 to 2017 and hand searched the reference lists of included studies. Eligibility criteria for selecting studies: Cohort and case–control studies that quantitatively examined the association of wholegrains or wholegrain foods with CVD outcomes in healthy adults or children. Results: 21 of the 22 studies had a serious or critical risk of bias. Studies with industry ties more often had favourable results compared with those with no industry ties, but the Confidence Interval (CI) was wide, Risk Ratio (RR)=1.44 (95% CI 0.88 to 2.35). The same association was found for study conclusions. We did not find a difference in effect size (magnitude of RRs) between studies with industry ties, RR=0.77 (95% CI 0.58 to 1.01) and studies with no industry ties, RR=0.85 (95% CI 0.73 to 1.00) (p=0.50) I 2 0%. These results were comparable for studies that measured the magnitude using Hazard Ratios (HR); industry ties HR=0.82 (95% CI 0.76 to 0.88) versus no industry ties HR=0.86 (95% CI 0.81 to 0.91) (p=0.34) I 2 0%. Conclusions: We did not establish that the presence of food industry sponsorship or authors with a COI with the food industry was associated with results or conclusions that favour industry sponsors. The association of food industry sponsorship or authors with a COI with the food industry and favourable results or conclusions is uncertain. However, our analysis was hindered by the low level of COI disclosure in the included studies. Our findings support international reforms to improve the disclosure and management of COI in nutrition research. Without such disclosures, it will not be possible to determine if the results of nutrition research are free of food industry influences and potential biases. PROSPERO registration number: CRD42017055841.